Images – Well-differentiated papillary mesothelioma of the tunica vaginalis - Gan, Ailsa May Li; Plantinga, Paul; Punjani, Nahid; Hussey, Andrew; Power, Nicholas (Canadian Urological Association Journal, 2018)
Well-differentiated papillary mesothelioma (WDPM) is a rare mesothelial tumour occurring in the tunica vaginalis of the testicle. The pathological classification of paratesticular mesothelial tumours is controversial and continues to evolve in the literature. Diagnostic criteria of one subtype, WDPM, are histological and include the following: 1) papillary or tubular-papillary architecture; 2) bland nuclear cytology; 3) low mitotic activity; 4) lined by a single row of cuboidal cells; and 5) absence of stromal invasion.1,2 This report presents issues of diagnosis of this rare pathology with imaging from an example case.